Electrically doped dynamically configurable field‐effect transistor for low‐power and high‐performance applications. Issue 16 (1st August 2015) - Lahgere, A.; Sahu, C.; Singh, J.
Abstract : The concept of an electrically doped dynamically configurable field‐effect transistor (FET) is presented, which provides freedom to dynamically switch between a high‐performance MOSFET and a low‐power tunnel FET that can be ideal for complementary circuit implementation. The charge carrier concentration, polarity and conduction mechanism of the device are precisely controlled by the appropriate application of an external polarity control signal, instead of the conventional ion‐implantation process. Two‐dimensional TCAD simulation results confirm the dynamic configuration of the proposed device and good functionality agreement with existing devices as well as it having the requisite qualities for low‐power and high‐performance applications.